Celebrity Society - van Krieken, Robert, author.
1 online resource (260 pages)
Keywords: On television and in films, in magazines and books, on the Internet and in the realm of politics, celebrities of all sorts seem to dominate our attention. Celebrity Society: The Struggle for Attention brings new perspectives to our understanding of how the figure of ‘the celebrity’ is bound up with the structure and dynamics of society, economics, and politics. It outlines how the ‘celebrification of society’ is not just the twentieth-century product of Hollywood and television, but a long-term historical process, beginning with Christian saints, the printing press, theatre, and art. Drawing on the ideas of Norbert Elias, the book explains how contemporary celebrity society is the heir (or heiress) of ‘court society’, taking on but also transforming many of the functions of the aristocracy. As well as examining celebrity in all the familiar arenas – film, television, music, fashion, and sport – Celebrity Society also includes the analysis of celebrity in business and management, politics, humanitarianism, and philanthropy. A key feature of the book is its development of the idea that celebrity is driven by the ‘economy of attention’, since attention has become a form of capital – attention capital –in the Information and Internet age. In this second edition the author has updated and significantly revised this path-breaking book to include a more detailed discussion of attention capital, the question of gender and celebrity, populism, fans, fandom, and self-formation, micro-celebrity, and personal or self-branding, the ‘worker celebrity’, and the impact of social media such as Twitter, Facebook, Instagram, and YouTube. Celebrity is an exciting and rapidly expanding field of social science, making this engaging book a valuable resource for students and scholars in sociology, politics, history, celebrity studies, cultural studies, the sociology of media, and cultural theory.